Prospects for the Development of Coconut Cooking Oil Household Business in Galang District, Deli Serdang Regency - Pinem, Nurul Fajriah; Nasution, Delima Lailan Sari; Pohan, Annisa Rizkia (Talenta Publisher, 2021)
Micro, small and medium enterprises (UMKM) in Indonesia have a very large and important contribution to the country's economy. UMKM currently running in the community consist of many fields, one of which is the use of Indonesian agricultural products. Coconut oil can be used as cooking oil, margarine and white butter ingredients, components in soap making and cosmetic formulations. UMKM producing coconut oil have considerable business opportunities, one of which is the Maida Coconut Cooking Oil Business which is located in Galang District, Deli Serdang Regency. The amount of coconut oil produced is still on a small scale. This is due to very simple equipment, high selling prices, and limited range of marketing strategies. This activity aims to help Maida UMKM to increase production by providing assistance in the form of tools and determining a reasonable cost of goods sold. The results showed that the cost of the product before adding equipment based on the full costing method was Rp. 41,746/L and the variable costing method was Rp. 39,236/L. Meanwhile, after adding tools based on the full costing method, it was Rp. 104,211/L and the variable costing method was Rp. 89,757/L.